RE-THINKING THE MYTH OF UNIVERSALITY IN RELIGIOUS LIBERTY: IS IT POSSIBLE THE HEGELIAN’S REVEALED RELIGION FROM THE PERSPECTIVE OF CONSTITUTIONAL LIBERALISM? - Gomez Pinto, Ricardo (Revista do Direito, 2023)
Recent decisions of the European Court of Human Rights and the Colombian Constitutional Court highlight the clash between Liberalism that adopts the idea of neutrality where a private interpretation of the constitution prevails. Herein, Liberalism assumes a universalising position that does not provide enough room for manoeuvre to other understandings and viewpoints different from the occidental standpoint. Such will be the case law concerned with both the Islamic issues in some European countries and millennial cultural conceptions of indigenous communities in Colombia as part of different interpretations of freedom of thought and liberty of religion. In order to show this dialectical approach, Schmitt’s concept of politics and the revealed religion in Hegel will be of dramatic relevance to offer a pluralistic position and, on the other hand, point out the constitutional conflict embedded in these scenarios and, with it, the fake aspiration of moral neutrality in the politics and economics. It emphasize a paramount discussion for the current debates on freedoms and constitutional law.